The effects of physical characteristics on the fatigue level after repeated sprints in Turkish National Greco-Roman Cadet wrestlers - Yazıcı, Yakup; Arslan, Fethi; Ziyagil, Mehmet Akif; Sivrikaya, Kenan; Türkmen, Mehmet (Anadolu Univ, 2022)
Evaluation of repeated sprints induced fatigue levels of Greco-Roman wrestlers according to their weight and height categories will help trainers in preparing athlete specific training programs. So this study aims to determine the effects of physical characteristics on the fatigue level of Turkish National Greco-Roman Cadet Wrestlers after 10 repeated sprints test (RST). The data were collected from 25 male wrestlers. Short sprint or reduction in sprint speed level was tested by RST. One way ANOVA was used for more than two groups. A Paired t-test was used for comparing of first two sprints to last two sprints with respect to 10 and 20 meters. The results of this study showed that significant differences were observed in all physical characteristics with respect to body weight and height classes in cadet wrestlers. While there is no difference in RST averages depending on body weight categories, there were significant differences in 3th, 4th and 5th sprints in 10 meters, 2th, 3th and 4th sprints in 20 meters according to height categories. Both of LBWC and MBWC had a lower RST induced fatigue levels than HBWC in 10 m and 20 m sprints. In contrast, both of MBHC and HBHC had a higher RST induced fatigue levels than SBHC in 10 m and 20 m sprint. In conclusion, the intensity of loadings, number and duration of explosive sprints and rest periods in at least two different groups for light weight class or short body height class and other cadet wrestlers should be based on their RST fatigue levels.
Keywords: Cadet Wrestling; Repeated sprints; Fatigue; Performance; Fitness